2007
DOI: 10.3892/ijmm.20.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of fatty acid metabolism-related gene expression in nonalcoholic fatty liver disease

Abstract: Abstract. Nonalcoholic fatty liver disease (NAFLD) is one of the most frequent causes of abnormal liver dysfunction, and its prevalence has markedly increased. We previously evaluated the expression of fatty acid metabolism-related genes in NAFLD and reported changes in expression that could contribute to increased fatty acid synthesis. In the present study, we evaluated the expression of additional fatty acid metabolism-related genes in larger groups of NAFLD (n=26) and normal liver (n=10) samples. The target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
308
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(343 citation statements)
references
References 30 publications
26
308
1
1
Order By: Relevance
“…In an experiment using rats fed a highfat diet, the mRNA expression of lipogenic enzymes including hepatic FASN was down-regulated by dietary levan, while hepatic PPARα mRNA expression was up-regulated by dietary levan (7). It was also reported that the gene expression of lipogenic enzymes including FASN was increased while that of PPARα was decreased in nonalcoholic fatty liver patients as compared with normal subjects (10).…”
Section: Resultsmentioning
confidence: 93%
“…In an experiment using rats fed a highfat diet, the mRNA expression of lipogenic enzymes including hepatic FASN was down-regulated by dietary levan, while hepatic PPARα mRNA expression was up-regulated by dietary levan (7). It was also reported that the gene expression of lipogenic enzymes including FASN was increased while that of PPARα was decreased in nonalcoholic fatty liver patients as compared with normal subjects (10).…”
Section: Resultsmentioning
confidence: 93%
“…Malonyl-CoA production is regulated by ACC1 and ACC2, while degradation is dependent upon the activity of malonyl-CoA decarboxylase (MCD). ACC1 234:1 expression and activity increases in fatty liver disease, while ACC2 expression is independent of hepatic lipid accumulation (Yahagi et al 2005, Kennedy et al 2007, Kohjima et al 2007). This increase in total ACC activity increases malonyl-CoA synthesis, hepatic malonyl-CoA concentration and flux through fatty acid synthesis (Zhao et al 2009).…”
Section: The Interplay Of Dnl and Beta-oxidationmentioning
confidence: 99%
“…Therefore, it is important to understand the features of lipid metabolism, particularly fatty acid metabolism, in NAFLD. Previously, we evaluated the expression levels of genes involved in fatty acid metabolism in the liver with NAFLD and found that the expression of those genes including acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS), was up-regulated, indicating that fatty acid synthesis was enhanced in hepatocytes, leading to the accumulation of fatty acids (9,10).…”
Section: Introductionmentioning
confidence: 99%